Impact of posttraumatic stress syndrome disorder on GPA for Kurd-Yazidis students studying at Duhok Polytechnical University - Alibrahim, Mohamed Sadeq Younes Morad (Journal of Educational and Psychological Sciences, 2021)
This study shows the impact of post-traumatic syndrome on the cumulative rate of students studying at Duhok Polytechnic University. The 314 students from different departments at Duhok Polytechnic University are targeted randomly selected. In order to answer the hypotheses of the study, the computational averages, the Pearson correlation coefficient, and the use of the T-test were used where the results indicated the following: The increase in post-traumatic stress syndrome is associated with an increase in mental unit feeling. The level of mental unity is higher in the group of two sources compared to the group of non-traumatized people. The existence of statistical differences between males and females in the level of the post-traumatic stress syndrome, and this is higher among females. The existence of statistical differences between males and females in the low cumulative rate of male and female enrollment and this is higher for females. In the light of the results, a number of recommendations and proposals have been formulated that could contribute to improving student coping with a post-traumatic syndrome, improving the cumulative rate and improving social communication.